RANKL‐Induced Increase in Cathepsin K Levels Restricts Cortical Expansion in a Periostin‐Dependent Fashion: A Potential New Mechanism of Bone Fragility. (28th April 2021) - Bonnet, Nicolas; Douni, Eleni; Perréard Lopreno, Geneviève; Besse, Marie; Biver, Emmanuel; Ferrari, Serge
ABSTRACT: Receptor activator of nuclear factor‐κΒ ligand (RANKL) is necessary and sufficient to promote osteoclastogenesis and a key pathogenic factor in osteoporosis. Failure of periosteal apposition to compensate for bone loss due to endosteal resorption further contributes to bone fragility. Whether these two processes are biologically related, however, remains unknown. Using high‐resolution peripheral quantitative computed tomography (HR‐pQCT), we first examined cortical bone parameters at distal radius and tibia in postmenopausal women (PMW) as well as in cadaveric human adult humeri. Increases in medullary area were negatively correlated with cortical bone volume but positively with total bone volume, and this relationship was stronger in the dominant arm, suggesting a mechanically driven process. To investigate the role of RANKL in this dual process, we used mice overexpressing huRANKL ( huRANKLTg + ). Trabecular and cortical bone volume (Ct.BV) are reduced in these mice, whereas cortical total volume (Ct.TV) is increased. In these bones, Sost mRNA levels are downregulated and periostin (Postn) mRNA levels upregulated, hence providing a positive message for periosteal bone formation. In turn, genetic deletion of Postn in huRANKLTg +  mice prevented the increase in Ct.TV and aggravated bone fragility. In contrast, cathepsin K (Ctsk) ablation improved Ct.TV in both huRANKLTg +  and wild‐type (WT) mice and stimulated periosteal bone formation, while augmenting Postn protein levels. Therefore, bone strength in huRANKLTg + /Ctsk −/− mice was restored to WT levels. These findings suggest that high levels of RANKL not only induce endosteal bone loss but may somewhat restrict periosteal bone formation by triggering periostin degradation through cathepsin K, hence providing a biological mechanism for the observed limited increase in cortical area in postmenopausal women. © 2021 American Society for Bone and Mineral Research (ASBMR).